2014
DOI: 10.1186/s13047-014-0050-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes following ankle fracture: a cross‐sectional observational study

Abstract: BackgroundThe purpose of the current study was to examine objective and subjective differences between three severity groups of ankle fractures patients compared to healthy controls.MethodsThis was a case-controlled study. 92 patients with an ankle fracture injury of which 41 patients were eligible to participate in the study. 72 healthy people served as controls. All patients underwent a computerized gait test, completed self-assessment questionnaires (The Foot and Ankle Outcome Score (FAOS) and the SF-36), e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
63
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 44 publications
(34 reference statements)
4
63
0
1
Order By: Relevance
“…This might have resulted from guarding or bracing by the patient (i.e., patient's fear of weightbearing and joint movement). These findings are congruent with the work by Segal et al (10), which showed decreased gait velocity among patients with an ankle fracture compared with the control group.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This might have resulted from guarding or bracing by the patient (i.e., patient's fear of weightbearing and joint movement). These findings are congruent with the work by Segal et al (10), which showed decreased gait velocity among patients with an ankle fracture compared with the control group.…”
Section: Discussionsupporting
confidence: 93%
“…The results, however, have been conflicting (10,(14)(15)(16). Most used self-assessment questionnaires and functional scores to evaluate the functional status of patients after ankle fracture surgery.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…The use of computerized gait analysis as a method to assess different musculoskeletal conditions is growing as it allows an objective assessment of the patient's functional ability and symmetry. Gait analysis deviations have been reported for patients following ankle fracture [22], post-anterior cruciate ligament reconstruction [23], and other lower extremity trauma [24]. All of the above have demonstrated the effect of injury on gait patterns of the patients compared to healthy controls.…”
Section: Discussionmentioning
confidence: 93%